Search for e + e − → K S 0 K S 0 h c $$ K_S^0K_S^0{h}_c $$ - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics)
Abstract Using e + e − collision data at 13 center-of-mass energies ranging from 4.600 to 4.951 GeV collected with the BESIII detector, we conduct the first search for the e + e − → K S 0 K S 0 h c $$ {K}_S^0{K}_S^0{h}_c $$ process and investigate the resonance structures in the cross section line shape. No significant signal is observed, and the upper limits of the Born cross sections at each center-of-mass energy are presented. The ratio σ e + e − → K S 0 K S 0 h c σ e + e − → K S 0 K S 0 J / ψ $$ \frac{\sigma \left({e}^{+}{e}^{-}\to {K}_S^0{K}_S^0{h}_c\right)}{\sigma \left({e}^{+}{e}^{-}\to {K}_S^0{K}_S^0J/\psi \right)} $$ is determined to be 0.15 ± 0.22. This result indicates that if vector states exist in this energy region, their decay into h c is significantly suppressed compared to decays into J/ψ.